DGGE fingerprinting of bacteria in soils from eight ecologically different sites around Casey Station, Antarctica - Chong, C.W.; Tan, G.Y.A.; Wong, R.C.S.; Riddle, M.J.; Tan, I.K.P. (2009)
Bacterial community structures in soils collected from eight sites around Casey Station, Antarctica, were investigated using denaturing gradient gel electrophoresis (DGGE) of amplified 16S rRNA gene fragments. Higher bacterial diversity was found in soils from protected or relatively low human-impacted sites in comparison to highly impacted sites. However, the highest diversity was detected in samples from Wilkes Tip, a former waste disposal site that has been undisturbed for the last 50 years. Comparison of community structure based on non-metric multidimensional scaling plots revealed that all sites, except the hydrocarbon-contaminated (oil spill) site, were clustered with a 45 similarity. A total of 23 partial 16S rRNA gene sequences were obtained from the excised DGGE bands, with the majority of the sequences closely related to those of the Cytophaga-Flexibacter-Bacteroides group. No significant correlation was established between environmental variables, including soil pH, electrical conductivity, carbon, nitrogen, water content and heavy metals, with bacterial diversity across the eight study sites.